A general strategy for semiconductor quantum dot production. Issue 17 (15th April 2021) - Xu, Yuanqing; Wang, Weibiao; Chen, Zhexue; Sui, Xinyu; Wang, Aocheng; Liang, Cheng; Chang, Jinquan; Ma, Yanhong; Song, Luting; Jiang, Wenyu; Zhou, Jin; Liu, Xinfeng; et al.
Abstract : Bulk semiconductors are readily obtained by chemical precipitation. The as-obtained bulk semiconductors are then mechanically tailored into semiconductor quantum dots. Abstract : Mass production of semiconductor quantum dots (QDs) from bulk materials is highly desired but far from being satisfactory. Herein, we report a general strategy to mechanically tailor semiconductor bulk materials into QDs. Semiconductor bulk materials are routinely available via simple chemical precipitation. From their bulk materials, a variety of semiconductor ( e.g., lead sulfide (PbS), cadmium sulfide (CdS), copper sulfide (CuS), ferrous sulfide (FeS), and zinc sulfide (ZnS)) QDs are successfully produced in high yields (>15 wt%). This is achieved by a combination of silica-assisted ball-milling and sonication-assisted solvent treatment. The as-produced QDs show intrinsic characteristics and outstanding water solubility (up to 5 mg mL −1 ), facilitating their practical applications. The QD dispersions present remarkable photoluminescence (PL) with exciton-dependence and nanosecond (ns)-scale lifetimes. The QDs-poly(methyl methacrylate) (PMMA) hybrid thin films demonstrate exciting solid-state fluorescence and exceptional nonlinear saturation absorption (NSA). Absolute modulation depths of up to 58% and saturation intensities down to 0.40 MW cm −2 were obtained. Our strategy could be applied to any semiconductor bulk materials and therefore paves the way for the construction of the complete library of semiconductor QDs.